An exploratory study of types of innovation in US foundations - Kristina Jaskyte Bahr (Administrative Sciences, 2019)
While foundations contribute in significant ways to the United States' social, economic, and political life, they are experiencing increasing demands placed upon them by their own sector and need to respond to the major changes in their external environment. In order to create breakthrough solutions to long-standing problems, foundations have to become more innovative and seek to experiment and find new approaches. Unfortunately, innovation discourse within foundations has received little attention. This paper fills the gap in the literature as it describes the results of a study that explored different types of innovations implemented in foundations. More specifically, staff members of 17 US foundations that are known for supporting innovation in nonprofit organizations, were asked to describe programmatic and administrative innovations implemented in their own foundations. The results showed that foundations that support innovation are in fact innovative themselves. They implemented numerous innovations in programmatic and administrative, financial, and structural areas. This paper provides a rich description of a broad range of innovations implemented within each of those areas. The contribution of this study and insights are significant at this particular time when foundations' roles and impact on social change are questioned. The results can enrich our discussion of where foundations can go from here in terms of becoming innovative themselves in order to be able to support and enhance innovation in the nonprofit sector.
Keywords: 350; foundations; innovation; nonprofit organizations; types of innovations